Polymorphisms in Base Excision Repair Genes Are Associated With Endometrial Cancer Risk Among Postmenopausal Japanese Women. Issue 9 (1st November 2013) - Hosono, Satoyo; Matsuo, Keitaro; Ito, Hidemi; Oze, Isao; Hirose, Kaoru; Watanabe, Miki; Nakanishi, Toru; Tajima, Kazuo; Tanaka, Hideo
Abstract : Objectives: Polymorphisms in base excision repair (BER) genes are associated with risk for several types of cancers but have not been studied with respect to endometrial cancer among Japanese women. Therefore, we conducted a case-control study to explore the association between polymorphisms in BER genes and the risk for endometrial cancer. Methods/Materials: This study included a total of 91 postmenopausal subjects with endometrial cancer and 261 controls without cancer who visited the Aichi Cancer Center between 2001 and 2005. We focused on single nucleotide polymorphisms within coding regions of 5 BER genes ( OGG1, MUTYH, XRCC1, APEX1, and PARP1 ). To assess lifestyle in the etiology of endometrial cancer, we used a self-administered questionnaire. Associations were evaluated using multivariate unconditional logistic regression models. We also assessed whether there were intergenic associations or an interaction with obesity. Results: We observed a significant association between endometrial cancer risk and XRCC1 rs1799782 (C > T, Arg194Trp) and XRCC1 rs25487 (G > A, Arg399Gln). We uncovered a significant association between obesity (body mass index, ≥25) and rs25487. The XRCC1 polymorphisms were in complete linkage disequilibrium, and the XRCC1 haplotype TG associated significantly with endometrial cancer risk. The interaction between the CA haplotype and body mass index was marginally significant, whereas interaction between haplotype in XRCC1 and rs1136410 ( PARP1 ) was not significant. Conclusions: We found a significant association between endometrial cancer risk and XRCC1 polymorphisms and haplotype TG in postmenopausal Japanese women.